Modelling of conformational change within photosynthetic reaction center of Rb. sphaeroides bacteria - P. A. Mamonov; P. M. Krasilnikov; P. P. Knox; Andrei B. Rubin (Компьютерные исследования и моделирование, 2009)
A possible conformational change, which accompanies electron tranport in Rb. sphaeroides photosynthetic reaction center (RC), was studied using quantum-chemical approach. A kinetic model which takes into account two conformational states of RC is proposed. The model quantitatively describes experimental temperature dependencies of recombination reaction rate P+QA- PQA. Quantum-chemical modeling of primary quinone (QA) binding site permits one to propose a minor shift of QA as a conformational change of interest. The shift is accompanied by break of a hydrogen bond between 4-C=O group of QA and histidine M219, and formation of a new hydrogen bond between QA and hydroxyl group of threonine M222. Characteristics of this conformational change were obtained from quantum-chemical calculations and match parameters of kinetic model in qualitative fashion.